Women of color in the South African workforce: workplace bias and its consequences - Mtya, Busisiwe (University of the Witwatersrand, Johannesburg, 2024)
This research study investigates the significance of women of colour in the South Africanworkplace by examining the impact of workplace bias and its consequences. The study takesan intersectional approach, considering the unique experiences and challenges faced bywomen of color in the workforce. The transactional model of coping and multi-level biastheories are employed to analyse the coping mechanisms employed by women of color andthe organizational and societal factors that contribute to bias. This research utilizes aqualitative survey methodology, specifically targeting MBA women of color from WitsBusiness School, who are employed in various industries across South Africa. The surveyaims to capture data on participants' experiences of workplace bias, coping strategies, and theconsequences of bias on their professional growth and well-being.Data collection from the survey questionnaire will be analysed using thematic analysistechniques to examine the correlation between workplace bias, coping strategies, andoutcomes such as career advancement, job satisfaction, and mental health. The study seeks toidentify the specific types of bias experienced by women of color and explore how thesebiases impact their career trajectories and overall well-being. Study findings are expected toprovide a better comprehension of the difficulties faced by women of colour in the SouthAfrican workforce and shed light on the effectiveness of coping strategies in mitigating thenegative consequences of bias. Moreover, the research aims to provide insights fororganizations and policymakers to develop interventions and strategies that promoteinclusivity and equality in the workplace, leading to a more diverse and equitable workforcein South Africa.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Women of color; South African workforce; Workplace bias; Intersectionality; Transactional model of coping; Multi-level bias theories; SDG-5: Gender equality